Comparing the quality of life in insulin recipient and refusal patients with type 2 diabetes - Mitra Khalili; Fakhri Sabouhi; Parvaneh Abazari; Ashraf Aminorroaya (Wolters Kluwer Medknow Publications, 2016)
Background: Better control of blood sugar and reduction of diabetes complications through insulin therapy could convince people to choose this method. However, patients might refuse insulin therapy due to its painful injection, limitations in daily activities, and hypoglycemia. Thus, insulin therapy could have both positive and negative effects on patients' quality of life (QOL). Therefore, the aim of this study was to compare the QOL of insulin recipient and insulin refusal patients with type 2 diabetes. Materials and Methods: This study was a descriptive and comparative research conducted on 126 patients; 63 were insulin recipients and 63 had refused insulin therapy. Participants were under the care of the Endocrine and Metabolism Research Center of Isfahan, Iran. Data were gathered using the Diabetes Quality of Life (DQOL) questionnaire. In this tool, higher scores indicated lower QOL in patients. Data were analyzed using independent t-test, analysis of covariance, Mann-Whitney, Chi-square, and Pearson and Spearman's correlation. Results: There was a significant difference (P < 0.001) between insulin recipient patients (mean = 2.02, SD = 0.31) and insulin refusal patients (mean = 1.74, SD = 0.41) in terms of mean QOL score. In addition, men and participants with higher educational levels reported a better QOL (P < 0.001). Conclusions: Results showed that insulin refusal patients had a better QOL. It seems that QOL is associated with the acceptance or refusal of insulin therapy. Therefore, enhancement of QOL could be related to all aspects of the disease, especially its treatment method and solving the therapeutic problems.